Les « règlements intérieurs » de village en Kabylie : entre maintien d’un droit coutumier et dynamiques nouvelles des communautés villageoises - Malika Assam (Revue des Mondes Musulmans et de la Méditerranée)
We propose here some thoughts about the recent issues that village communities face up to in Kabylia, from the study of five « village bylaws » collected during fieldwork in Djurdjuran Kabylia. These documents arise from the writing in French and in an original form of customary law, originally oral and elaborated by the political, administrative and judicial body of the village (the djemaa). Revealing the sustainability of village institutions, which became informal after 1871, but also their profound transformation, those documents can identify their current role, thanks to the regulations they still contain. But they also include many explanations showing the work of reflexivity led by stakeholders who rely on old principles such as the importance of the village personality, but also integrate modern references to politics, identity and memory.